OFR-8-77 Effects Of Temperature And Humidity Variations On The Stability Of Coal Mine Roof Rocks - I. Introduction - A. Statement Of The Problem - Charles D. Haynes (The National Institute for Occupational Safety and Health (NIOSH), 1975)
Outside air for ventilating coal mines in Alabama varies considerably in both temperature and moisture content during the year. Alternate condensation and evaporation of the moisture on mine roofs may result in stresses detrimental to the strength of mine roof. It is well known that the clays in shales absorb moisture, and many investigations have noted the weakening of shales by absorption of moisture. Parker (1970) concluded that there is an annual cycle of rock deterioration in mine roof rock caused by the annual temperature-humidity cycle at the surface. He further noted that moisture reduces the strength of dry rock by one-half, that moisture added to dry rock can cause failure in compression, and that drying of wet rock causes tensile stress buildups by shrinkage. His recommendations for alleviating the moisture-temperature problem was to seal the rock in critical areas and to control ventilation so that air temperature will be lower than rock temperature. The latter recommendation will avoid condensation on the rock surfaces. Hartmann and Greenwald (1941) published the results of a very comprehensive experimental project to determine the effect of temperature and humidity changes on the behavior of mine roof. Their general conclusions included statements that roof rocks were very sensitive to moisture changes, but had low coefficients of thermal expansion. The coefficients were twice in the direction normal to the bedding plane as compared to the parallel